Theoretical basis of the study of the problem of self-education of personality in psychology (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article, which based on the theoretical justification ofscientific literature, presents a theoretical analysis of the problem ofperson’s self-education. There was determined the conceptual categoricalapparatus and also some essential features of the process of self-educationwere revealed. The structure and dynamics of self-education’s process inthe context of the category of self-awareness are revealed. The role ofself-knowledge, self-regulation, self-alignment, self-esteem in the directionof positive personality transformations is especially emphasized. It wasestablished that the processes of self-education and self-regulation areconscious practical actions which are aimed at a more complete realizationby a human of himself as a person. Prospects for further research areoutlined.
Keywords: self-education; self-knowledge; self-regulation; personal changes; self-esteem